A Polymorphism in C-C Chemokine Receptor 5 (CCR5) Associates with Löfgren’s Syndrome and Alters Receptor Expression as well as Functional Response - Bekir Karakaya; Coline H. M. van Moorsel; Marcel Veltkamp; Claudia Roodenburg-Benschop; Karin M. Kazemier; Annette H. M. van der Helm-van Mil; Tom W. J. Huizinga; Jan C. Grutters; Ger T. Rijkers (Cells, 2021)
C-C chemokine receptor 5 (CCR5) and polymorphisms in CCR5 gene are associated with sarcoidosis and Löfgren’s syndrome. Löfgren’s syndrome is an acute and usually self-remitting phenotype of sarcoidosis. We investigated whether the single nucleotide polymorphism (SNP) rs1799987 is associated with susceptibility for Löfgren’s syndrome and has an effect on CCR5 expression on monocytes and function of CCR5. A total of 106 patients with Löfgren’s syndrome and 257 controls were genotyped for rs1799987. Expression of CCR5 on monocytes was measured by flowcytometry. We evaluated calcium influx kinetics following stimulation upon N-formylmethionyl-leucyl-phenylalanine (fMLP) and macrophage inflammatory protein-1α (MIP-1α) on monocytes by measuring the median fluorescence intensity (MFI). The frequency of the G allele of rs1799987 was significantly higher in Löfgren’s syndrome than in healthy controls (p = 0.0015, confidence interval (CI) 1.22–2.32, odds ratio (OR) 1.680). Patients with a GG genotype showed higher CCR5 expression on monocytes than patients with the AA genotype (p = 0.026). A significantly (p = 0.027) lower count of patients with the GG genotype showed a calcium influx reaction to simulation upon MIP-1 α, compared with patients with the AA genotype. The rs1799987 G allele in CCR5 gene is associated with susceptibility to Löfgren’s syndrome and with quantitative and qualitative changes in CCR5, potentially effecting the inflammatory response.